THE MODEL OF DEVELOPING INFORMATION TECHNOLOGICAL COMPETENCE IN FUTURE TEACHERS - Begmatova Sevara Nematovna (Scholars Digest Publishing, 2023)
This article describes the model, directions, levels, criteria for the development of information technology competencies in future teachers in the context of modernization of the higher education system.
Keywords: This article describes the model, directions, levels, criteria for the development of information technology competencies in future teachers in the context of modernization of the higher education system.